2017
DOI: 10.3738/1982.2278.1686
|View full text |Cite
|
Sign up to set email alerts
|

Indução Da Frutificação Paternocárpica De Frutos Em Híbrido De Abóbora Japonesa Com 2,4-D Sob Condições De Temperatura Elevada

Abstract: O objetivo do trabalho foi avaliar o efeito de doses de 2,4-D (ácido 2,4-diclorofenoxiacético) na produção de frutos de abóbora japonesa em Gurupi -TO. O delineamento experimental utilizado foi de blocos casualizados com oito tratamentos e quatro repetições. Foram testadas sete doses do regulador vegetal em baixa concentração aplicado na forma de 2,4-D, nas seguintes concentrações 187,5; 200; 212,5; 225; 237,5; 250 e 262,5 mg.L -1 e mais a testemunha (polinização com pólen) feita de forma manual. Avaliou-se pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…O principal centro de diversidade da abóbora é o continente americano, mais precisamente a área central do México. As abóboras consistem em plantas de clima quente, com temperaturas ótimas para o desenvolvimento e frutificação, variando de 20 a 27 ºC (Ferreira et al, 2017). Conforme Amaro et al (2014), a abóbora conhecida como 'Tetsukabuto' ou 'Cabotiá' é um híbrido interespecífico, resultado do cruzamento entre linhagens selecionadas de moranga (Cucurbita maxima Duch.…”
Section: Introductionunclassified
“…O principal centro de diversidade da abóbora é o continente americano, mais precisamente a área central do México. As abóboras consistem em plantas de clima quente, com temperaturas ótimas para o desenvolvimento e frutificação, variando de 20 a 27 ºC (Ferreira et al, 2017). Conforme Amaro et al (2014), a abóbora conhecida como 'Tetsukabuto' ou 'Cabotiá' é um híbrido interespecífico, resultado do cruzamento entre linhagens selecionadas de moranga (Cucurbita maxima Duch.…”
Section: Introductionunclassified
“…The average yield obtained with the 300 kg ha −1 dose of P2O5 in the second growing season is higher than the average yield observed for the state of Minas Gerais of 15 ton ha −1 (Sediyama et al, 2009), however. Lower than the average productivity observed by Ferreira et al (2017), for the state of Tocantins.…”
mentioning
confidence: 57%
“…The use of the synthetic cytokinin forchlorfenuron (CPPU) resulted in good quality production for several fruit species, this effect being confirmed by Ding et al (2013) in tomatoes, Li et al (2017) in cucumber and Zhang et al (2017) in kiwi. As well as the use of synthetic auxins, aiming at asexual production for the formation of parthenocarpic fruits, as stated by Ferreira et al (2017) with the use of dichlorophenoxyacetic acid (2,4-D) in Japanese pumpkin. Pereira et al (2014), working with 'Gefner' atemoya, observed that the exogenous application of 1-naphthalene acetic acid (NAA), associated with gibberellic acid promoted high fruiting in a similar way to artificial pollination.…”
Section: Introductionmentioning
confidence: 99%